The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/jhep11(2020)114
|View full text |Cite
|
Sign up to set email alerts
|

Towards spacetime entanglement entropy for interacting theories

Abstract: Entanglement entropy of quantum fields in gravitational settings is a topic of growing importance. This entropy of entanglement is conventionally computed relative to Cauchy hypersurfaces where it is possible via a partial tracing to associate a reduced density matrix to the spacelike region of interest. In recent years Sorkin has proposed an alternative, manifestly covariant, formulation of entropy in terms of the spacetime two-point correlation function. This formulation, developed for a Gaussian scalar fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…[13,14,17] Consequently, we conjecture that, for those circuits, the entanglement entropy can be computed through (48). The results so obtained would be compared with recent results in the literature [19,26,27] dealing with entanglement entropy in interacting theories.…”
Section: Cmera and Holographymentioning
confidence: 91%
“…[13,14,17] Consequently, we conjecture that, for those circuits, the entanglement entropy can be computed through (48). The results so obtained would be compared with recent results in the literature [19,26,27] dealing with entanglement entropy in interacting theories.…”
Section: Cmera and Holographymentioning
confidence: 91%
“…The author showed that a consistent renormalization can be performed, providing finite contributions to the entanglement entropy at one loop. In [7], in a quantum mechanical setting consisting on quartic perturbative perturbations on the harmonic oscillator free case, the replica trick was used to check that to first order in perturbation theory, the entanglement entropy can be computed by means of the perturbatively corrected version of the two point correlation functions of the system.…”
Section: Jhep02(2021)106mentioning
confidence: 99%
“…where q,p ≡ and a,a † ≡ indicate that the RHS corresponds to the matrix representation with respect to one of the two standard bases (55) or (54). Note that these standard bases are only determined up to an overall group transformation in G that will preserve the respective structures.…”
Section: Abstract Algebra Of Observablesmentioning
confidence: 99%
“…The entanglement entropy of a non-Gaussian state will in general also depend on higher npoint functions, so we cannot use (230) anymore. Interestingly, if we perturb a Gaussian state in a non-Gaussian way, the entanglement entropy will at linear order only feel the Gaussian part of the perturbation [55], so that we can use the linearization of (230) to deduce the linear change…”
Section: The Restricted Covariance Matrix Satisfiesmentioning
confidence: 99%